2008
DOI: 10.1111/j.1365-2052.2008.01748.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis reveals high genetic diversity but low genetic structure in Ethiopian indigenous cattle populations

Abstract: Ethiopian cattle are under threat from uncontrolled mating practices and are at high risk of becoming genetically homogeneous. Therefore, to evaluate genetic diversity, population structure and degree of admixture, 30 microsatellite markers were genotyped using 351 DNA samples from 10 Ethiopian cattle populations and the Holstein breed. The mean number of alleles per cattle population ranged from 6.93 +/- 2.12 in Sheko to 7.50 +/- 2.35 in Adwa. The mean observed and expected heterozygosities were 0.674 +/- 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
50
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 26 publications
13
50
6
Order By: Relevance
“…Similar to our results, F ST values of 1.2% (Dadi et al, 2008) and 1.1% (Zerabruk et al, 2011) from microsatellite markers, and 1.2% from a low-density taurine-derived chip (Edea et al, 2013), were reported among Ethiopian cattle populations. However, our F ST values were lower than those from previous studies of West African cattle breeds (6%; IbeaghaAwemu and Erhardt, 2005) and six African cattle breeds (4%; Gautier et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to our results, F ST values of 1.2% (Dadi et al, 2008) and 1.1% (Zerabruk et al, 2011) from microsatellite markers, and 1.2% from a low-density taurine-derived chip (Edea et al, 2013), were reported among Ethiopian cattle populations. However, our F ST values were lower than those from previous studies of West African cattle breeds (6%; IbeaghaAwemu and Erhardt, 2005) and six African cattle breeds (4%; Gautier et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Recent molecular studies have characterized Ethiopian cattle breeds by using a limited number of low-density microsatellites, mitochondrial DNA (mtDNA) or Y-chromosome markers (Li et al, 2007;Dadi et al, 2008;Zerabruk et al, 2011). To date, Bangladeshi cattle populations have not been subjected to thorough molecular investigation; however, limited study of the Red Chittagong population has been conducted using mtDNA (Bhuiyan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…3). High levels of admixture in Niger cattle were strongly evident and consistent with the reports on other African cattle (Dadi et al, 2008;Ndiaye et al, 2015). A general point of view is that the B. indicus first entered the African continent via the Suez route from Arabia (Epstein and Mason, 1984) and maritime routes to the Horn of Africa (Hanotte et al, 2002).…”
Section: Individual Assignment In Niger Cattlesupporting
confidence: 71%
“…Similarly, the pairwise allele sharing distance varied from 0.223 (Zebu Arabe-Kuri) to 0.259 (Zebu Bororo-Kuri) ( Table 3). The overall F ST observed in Niger cattle was much lower than that reported for Sudanese (F ST = 0.084; Hussein et al, 2015), Cameroonian (F ST = 0.061; Ngono Ema et al, 2014) and other West African cattle (F ST = 0.06; Freeman et al, 2004), while the estimate was relatively higher than that of Ethiopian cattle (F ST = 0.013; Dadi et al, 2008). Further, to evaluate within-and between-population diversities, pairwise allele sharing distances were calculated for all possible pairs of individuals within and across populations.…”
Section: Genetic Differentiation Among Niger Cattle Breedsmentioning
confidence: 42%
See 1 more Smart Citation